Building Creative Thinking Skills in Young Children Aged 3-4 Year Old Through Reading Storybooks - Sari, Dhea Intan Puspita (BELIA: Early Childhood Education Papers, 2020)
Living in an era that is changing so fast provides various challenges. In order not to be crushed by the times, humans must have several important abilities that can support them to survive, one of which is the ability to think creatively. This article discusses how to build creative thinking skills through reading story books from an early age. This article discusses the effectiveness of reading story books for children aged 3-4 years to build their creative thinking skills. This article was compiled using the literature review method from several international and national journals. From the results of the literature review, it was found that building creative thinking skills at an early age can be done through reading story books.